2020
DOI: 10.1016/j.cca.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cytokines and coagulation-related parameters in patients with coronavirus disease 2019 admitted to ICU

Abstract: Highlights Significant negative correlation between IL-6 and platelet parameters was discovered. Correlation between multiple cytokines and coagulation indicators was found. Pro-inflammatory factors were found to be more associated to coagulation parameters. Cytokines play an important role in the pathogenesis and evaluation of the condition of COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
4
15
0
Order By: Relevance
“…Some research has found that cytokines play an important role in the pathogenesis of COVID-19. Also, IL-6 seems more relevant in the evaluation of the condition of COVID-19 patients [23] . In addition to the core proteins such as IL-6 , which are involved in molecular docking simulation, the T-helper 1 cytokines ( IL1B, IFN-γ, IP10 , and MCP1 ) increase in patients infected by SARS-COV-2 [24] and other co-targeted genes such as IFNG and MAPK are also involved.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has found that cytokines play an important role in the pathogenesis of COVID-19. Also, IL-6 seems more relevant in the evaluation of the condition of COVID-19 patients [23] . In addition to the core proteins such as IL-6 , which are involved in molecular docking simulation, the T-helper 1 cytokines ( IL1B, IFN-γ, IP10 , and MCP1 ) increase in patients infected by SARS-COV-2 [24] and other co-targeted genes such as IFNG and MAPK are also involved.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol's ability to mitigate inflammation has also been suggested, owing to its suppressive action on interleukin 8 (IL-8), a circulating inflammatory cytokine. The relationship between increased proinflammatory cytokines and coagulopathy is intricate and has emerged as key player in the pathogenesis of COVID-19 [72]. Moreover, not only host factors have an impact on COVID-19-associated hemostatic disorders, but also specific viral proteins can significantly trigger the increase in pro-inflammatory cytokines, and consequently activation of the coagulation system [73].…”
Section: Resveratrol Modulates Thrombotic Markersmentioning
confidence: 99%
“…An excessive inflammatory response to SARS-CoV-2 is considered to be the major cause of disease severity and the high fatality rate among COVID-19 patients [ 13 ] and is associated with high levels of circulating cytokines, vascular leakage, and immune cell infiltration in the lungs, heart, and kidney [ 16 , 20 , 21 , 22 ]. Inflammatory cytokines such as TNF-α, interferon gamma (IFN-γ), interleukin 6 (IL-6), and IL-10 present in the plasma of COVID-19 patients [ 23 , 24 ] induce mitochondrial reactive oxygen species production and impede mitochondrial oxidative phosphorylation and ATP production [ 25 , 26 ] among other effects. This, in turn, may lead to mitochondrial membrane permeabilization, cell death, and multiple organ dysfunction, a syndrome observed in COVID-19 patients [ 27 ].…”
Section: Sars-cov-2-induced Covid-19mentioning
confidence: 99%